The Birds of the Air: The Pandemic and the Animal in Us - Barbaza, Remmon E (Archīum Ateneo, 2020)
Speaker: Dr. Remmon Barbaza The pandemic allows us to revisit a difficult question, as if we’re caught in a bind. On the one hand we recognize that we, too, are animals. On the other hand we also insist that we are superior to animals, and some would even go so far as to say that we are completely distinct from animals. Who are we then, we humans? And how do we stand in relation to animals, and therefore to the animal in us? -- Remmon E. Barbaza is an Associate Professor and former Chair, Department of Philosophy. He earned his PhD in Philosophy from the Munich School of Philosophy in Germany, with a dissertation, Heidegger and a New Possibility of Dwelling (Frankfurt: Peter Lang, 2003), under the supervision of the late Prof. Dr. Gerd Haeffner, S.J. His research interests include technology, the city, language, and translation.